Chronic temporomandibular joint pain: two cases of osteoid osteoma and a review of the literature. Issue 9 (September 2017) - Deferm, J.T.; Steens, S.C.A.; Vriens, D.; Bekers, E.M.; Kalaykova, S.I.; Borstlap, W.A.
Abstract: Osteoid osteoma is a benign bone tumour with self-limiting growth potential occurring in any part of the body. Two rare cases of a pathologically proven osteoid osteoma invading the temporomandibular joint (TMJ) are reported herein. This article also reviews the cases of osteoid osteoma of the craniofacial complex reported in the English-language literature to date. Although the clinical presentation of osteoid osteoma in the jaw differs from that of osteoid osteoma in the more common locations, the radiographic features are similar. In both cases presented, computed tomography revealed a small round osseous lesion with sharp margins in the TMJ. Bone scintigraphy was performed in order to differentiate the lesions from other osseous lesions. Both patients underwent surgical excision of the lesion with immediate relief of the pain. The importance of early recognition of the clinical and imaging characteristics of an osteoid osteoma of the TMJ is emphasized, in order to prevent misdiagnosis and avoid discouraging therapies.